MANAJEMEN PENGETAHUAN DAN TRANSFORMASI DIGITAL DI ERA INDUSTRI 4.0 - Muhammad Mujtaba Mitra Zuana; Sopiah Sopiah (ITB AAS INDONESIA Surakarta, 2022)
This article is an overview of the Systematic Literature Review (SLR) on Knowledge Management (KM), Digital Transformation (DT), and Industry 4.0, which defines the interactions, bonds, and interdependencies of these new research streams. Playing an important role in a progressive discipline, our research summarizes the state of the art past literature using a rigorous methodological approach. The researchers adopted the Scopus database in their analysis and used the Bibliometrix R package. The analysis revealed 761 peer-reviewed English articles. This study shows several research clusters: KM and DT; KM and innovation ecosystem; KM and border technology; and KM, decision making, and Industry 4.0. In addition, this article contributes to identifying growing areas of research that have uncovered previously unknown and interesting relationships between KM, DT, and the public sector. Therefore, the article emphasizes the important role of DT in the development of KM,, discusses future research perspectives as quantitative analysis and combines academics and practitioners.